2016
DOI: 10.1007/s11103-016-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

How plants handle multiple stresses: hormonal interactions underlying responses to abiotic stress and insect herbivory

Abstract: Adaptive plant responses to specific abiotic stresses or biotic agents are fine-tuned by a network of hormonal signaling cascades, including abscisic acid (ABA), ethylene, jasmonic acid (JA) and salicylic acid. Moreover, hormonal cross-talk modulates plant responses to abiotic stresses and defenses against insect herbivores when they occur simultaneously. How such interactions affect plant responses under multiple stresses, however, is less understood, even though this may frequently occur in natural environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(211 citation statements)
references
References 149 publications
(191 reference statements)
3
204
0
4
Order By: Relevance
“…Soil moisture may influence the impact of herbivores on plant performance (Gray & Steffey, 1998; Jamieson, Trowbridge, Raffa, & Lindroth, 2012) and chemistry (Erb & Lu, 2013; Nguyen, Rieu, Mariani, & van Dam, 2016). We found that WCR attack reduced plant height and accentuated the effect of low soil moisture on the onset of silk emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Soil moisture may influence the impact of herbivores on plant performance (Gray & Steffey, 1998; Jamieson, Trowbridge, Raffa, & Lindroth, 2012) and chemistry (Erb & Lu, 2013; Nguyen, Rieu, Mariani, & van Dam, 2016). We found that WCR attack reduced plant height and accentuated the effect of low soil moisture on the onset of silk emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout T-DNA insertion mutant of Osgsk1 (a rice GSK3/SHAGGY-like protein kinase gene, ortholog of AtBIN2/AtSK21, a negative regulator of BR-signaling), depicted enhanced tolerance towards abiotic stress, while OsGSK1 overexpression resulted in stunted growth in Arabidopsis (80). In addition, hormones target various members of protein families playing a significant role in growth either individually or in co-regulated manner, thereby indicating the synergistic action of metabolic pathways (81). Biotechnological manipulation of these key proteins could allow not only the adaptation under adverse environmental conditions, but also determine the flux in phytohormone biosynthesis for securing, in the long run, improved food production.…”
Section: (C) Manipulation Of Phytohormone Levelsmentioning
confidence: 99%
“…Plant resource condition, herbivore dynamics, phenological overlap with shared hosts and pollinators or competing predators, and timing of damage can influence the degree of plant tolerance (Kolb et al 2007;Wise and Abrahamson 2007;von Euler et al 2014;Lehndal and Ågren 2015;Krimmel and Pearse 2016;Stieha et al 2016;Kafle et al 2017). Co-occurring stressors may further interact with cumulative herbivory pressure to inhibit successful tolerance (Lay et al 2011;Nguyen et al 2016). Population-level effects of herbivory have been well-documented in C. canescens.…”
Section: Effect Of Cumulative Herbivory On Success Of Response Througmentioning
confidence: 99%